Influence of Combined Application of Inorganic N and P Fertilizers and Cattle Manure on Quality and Shelf-Life of Potato (Solanum tuberosum L.) Tubers - Masrie Z, Biruk; Dechassa R, Nigussie; Abebie, Bekele; Alemayehu, Yibekal; Tana, Tamado (Journal of Postharvest Technology, 2014)
Potato tuber qualities, including dry matter content, specific  gravity, total soluble solids, and crude protein content, are  important parameters for human consumption. Tuber  physiological weight loss, rotting, and sprouting during storage  are important aspects that influence the keeping quality of the  crop for profitable production. These tuber quality parameters can  be affected by fertilizer management in the sense that inadequate  or excess fertilizer application reduces tuber quality and shelf life. Therefore, a study was conducted during two successive  cropping seasons of 2012 and 2013 to determine the effect of  combined application of nitrogen, phosphorus, and cattle manure on potato tuber quality and shelf-life during storage.
Keywords: Physiological weight loss; Sprout to tuber weight ratio; Tuber dry matter content Tuber rotting; Tuber quality; Shelf-life